Optimasi Kendaraan Pengangkut Sampah di Kecamatan Kertapati Menggunakan Pemrograman Bilangan Bulat - Eka Susanti; Endro Setyo Cahyono; Oki Dwipurwani (Jurnal Matematika, 2016)
Waste management in the district Kertapati done by the private sector and government. The authorities responsible for waste management is Palembang City Sanitation Department (DKKP). Waste is transported from the area TPS (Transit Depo) to landfill Sukawinatan use two types of vehicles, namely dump trucks and armroll. Analyzed the optimal number of vehicles ritase waste carrier with the highest amount of waste as a goal. The total time of transport, the maximum capacity of conveyance and the maximum amount of waste that must be transported as an integer linear programming constraints. Completion of linear models using methods Branch and Bound. Volume of waste in Lambung 87 is 7630 kg, the optimal use of dumb truck with 2 ritase carriage. Volume of waste in the Lambung 42 as much as 8850 kg, optimal use armroll with 3 ritase carriage. The amount of waste in the Lambung 69 as much as 7770 kg, more optimal use of dumb truck with 2 ritase carriage.